Design and application of a fully automatic throat swab cartridge exit device for nucleic acid detection (一种用于核酸检测的全自动咽拭子弹出装置的设计与应用) - ZHU Kunkun (朱坤坤); XU Yuanle (许远乐); WANG Yuena (王岳娜); WU Bo (武博) (中西医结合护理)
This paper introduced the design and application of a fully automatic throat swab cartridge exit device for nucleic acid detection. The aim of this throat swab cartridge exit device is to improve the nucleic acid detection efficiency and reduce the risk of medical pollution diffusion. (本研究介绍一款用于核酸检测的全自动咽拭子弹出装置的设计原理与使用方法, 其在应对大规模核酸采样时, 能有效提升采样效率, 降低污染扩散风险。)